2015
DOI: 10.1111/gcbb.12280
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping in Salix viminalis L. (Salicaceae) – identification of candidate genes associated with growth and phenology

Abstract: Willow species (Salix) are important as short‐rotation biomass crops for bioenergy, which creates a demand for faster genetic improvement and breeding through deployment of molecular marker‐assisted selection (MAS). To find markers associated with important adaptive traits, such as growth and phenology, for use in MAS, we genetically dissected the trait variation of a Salix viminalis (L.) population of 323 accessions. The accessions were sampled throughout northern Europe and were established at two field site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 73 publications
1
33
1
Order By: Relevance
“…The cited authors developed QTL maps with the application of AFLP, RFLP, SNP and SSR markers. In the present experiment, a higher number of QTLs linked with plant height, shoot diameter and number of shoots per plant (11, 9 and 3 respectively) was identified than in other studies that relied on different types of markers [17,19]. The identified QTLs explained a lower percentage of variability in the analyzed traits (2.97%–16.16%) than those identified by other authors, which explained 14%–22% [17], 10%–20% [21] and 8%–42% of variability [18].…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…The cited authors developed QTL maps with the application of AFLP, RFLP, SNP and SSR markers. In the present experiment, a higher number of QTLs linked with plant height, shoot diameter and number of shoots per plant (11, 9 and 3 respectively) was identified than in other studies that relied on different types of markers [17,19]. The identified QTLs explained a lower percentage of variability in the analyzed traits (2.97%–16.16%) than those identified by other authors, which explained 14%–22% [17], 10%–20% [21] and 8%–42% of variability [18].…”
Section: Discussioncontrasting
confidence: 54%
“…RAPD and ISSR systems are universal tools that are highly useful at various stages of breeding new plant varieties. In the existing studies, willow loci were identified mainly in analyses of biomass yield [17,18,19,20,21]. Quantitative trait loci linked with the resistance/susceptibility of Salix species to leaf rust were rarely identified, including by Rönnberg-Wästljung et al [31], Hanley et al [26] and Samils et al [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale behind the first hypothesis presented in the study was that the non-dormant cuttings mobilize their carbohydrate reserves, which will be more depleted in non-dormant than dormant cuttings the later the planting date becomes, and that BCGDD is genetically determined and differs between willow clones [29,30]. The first hypothesis was partly supported by our results as BCGDD was significantly affected by willow clone during mid-and late planting dates (i.e., May 10 and 24, June 16).…”
Section: Discussionmentioning
confidence: 99%